Darboux integrability of a Mathieu-van der Pol-Duffing oscillator. (April 2023) - Cen, Zhihao; Xie, Feng
Abstract: In this paper, we characterize all the Darboux polynomials of a Mathieu-van der Pol-Duffing oscillator by transforming from the original system into a three dimensional system. We also provide a complete classification of the rational first integrals and of the Darboux first integrals through the analysis of its Darboux polynomials and its exponential factors.